About another (new) historical period and the urgency to think about other (new) analytical categories: applications in the urban-regional and intra-urban dimensions. - Ongaro, Nathália Giassetti; Silva Junior, Reinaldo Ricarte da; Silva Neto, Manoel Lemes da (Revista Nacional de Gerenciamento de Cidades, 2020)
Seeking to highlight new forms of analysis and construction of space in the historic period that is opening, some categories appear as central to this analytical claim. Project-concepts, such as used / practiced territory, present in the productions of Ana Clara Torres Ribeiro and Milton Santos are revealed as convergences of a common intellectual project. The understanding of space as the totalitarian group that apprehends systems of actions and systems of objects is one of the notions that guide the discussion. Immersed in this situation, two analytical axes stand out, materializing at different scales, but sharing the same problems in the State of São Paulo. The urban-regional dimension, responsible for revealing the dynamics and spatial organization in the State, contributes to the understanding of the region's instance as a group of municipalities that work together, and express in different ways their hegemony over the territory. The intra-urban dimension reveals a reality in which it is possible to observe this same hegemony, but in absolutely different ways. In the analysis of these two categories, the inequality and the hegemonic projects that were consolidated during the globalization phenomenon are always very explicit, allowed by an amazing social naturalization. The objective of the work, therefore, is to rescue the interdisciplinary dialogue between two central intellectuals of this type of spatial analysis, and permeate this spatial theory through the scales of the territory, appropriating key concepts that express, in the theoretical field, the urban counter-rationalities , which multiply and emerge in this new historical period.